(untitled) (Journal of Information Technologies in Education (ITE), 2016)
The article exposes developer’s point of view on minimizing creation, upgrade, postrelease problem solving time for applications and components, targeted to multiple operating systems, while keeping high end product quality and computational performance. Non-uniformity of analogous tools and components, available on different platforms,causes strong impact on developer’s productivity. In part., differences in 3rd-party component interfaces, versions, quality of distinct functions, cause frequent switching developer’s attention on issues not connected (in principle) with the target project. While loss of development performance because of attention specifics is more subjective value, at least physical time spent on tools/components misbehavior compensation and normal tools configuring is measurable. So, the main thesis verified is whether it’s possible to increase continuity of the development process by technical improvements only, and by which value. In addition, a novel experimental tool for interactive code execution is described, allowing for deep changes in the working program without its restart. Question under research:minimizing durations of programming-build-test-correct loop and small code parts runs, in part.,improving the debugging workflow for the account of combining the interactive editor and the debugger.